GREEN ISLAMIC MICROFINANCE: EMPIRICAL EVIDENCE FROM TUNISIA - Ben Salem, Asma (I-iECONS e-proceedings, 2023)
In the last decade, conventional microfinance institutions started to consider their environmental bottom line in addition to their financial and social objectives. Previous studies identify empirically the characteristics of conventional MFIs that are involved in environmental management in developed markets and their role in facing environmental and climate challenges in Arab countries. However, little is known about the triple bottom line of Islamic microfinance institutions. This paper aims to investigate the environmental performance of Islamic microfinance highlighting the synergies between Islamic microfinance and green inclusive finance. For that purpose, this research uses secondary data from multiple sources and descriptive data analysis. Basing our analysis on the Green Index framework to assess whether Tunisian Islamic MFIs are green institutions for the period between 2017 and 2021, we find growing scores of MFI’s environmental performance. The results provide empirical evidence of the Islamic microfinance contribution to sustainable finance in Tunisia. The results indicate that the institution shows the interest of its shareholders in initiating environmental strategy while conventional institutions are in the process of planning or developing products and strategies. Meanwhile, the institution provides green financings last year, the awareness of environmental opportunities and risks seem less evident for the management of the Islamic MFI. This study contributes to the ongoing debate of whether Islamic microfinance has a triple bottom line. This research also provides insight into the environmental performance of IMFI in Tunisia. The findings provide useful information to managers, investors, and policymakers.